The last kids on Earth and the doomsday race - Brallier, Max (Brallier, Max. Last kids on Earth ;, 2021)
Jack Sullivan's zombie-controlling powers are growing stronger, and he and his friends must take those powers to the mysterious Tower and stop Rezzoch the Ancient, Destructor of Worlds, from entering their world. First, though, they must confront the adventures that await them on the Mallusk, a giant centipede monster with the world's largest shopping mall on its back, complete with a thriving monster society inside it. Things spiral out of control until the only option Jack has is to run for mayor of Mallusk City.